The Difference in Contributing Factors and Costs Associated with Outpatient Refusal to Accept Cardiovascular Medications or Analgesics During Dispensing Process. - Mohamed Koya, M V; Koya, Saiful; Rahman Hazirah, Abd; Nurul Syahida, Radzuan (Iraqi Journal of Pharmaceutical Sciences, 2021)
Background: Study looking into cardiovascular disorders (CVD) medicines or analgesics cost-saving activities during dispensing process is lacking.Aim: To determine differences in factors and costs associated with refused CVD medicines or analgesics during dispensing processMethod: This study was approved by Medical Research and Ethics Committee (MREC) (Registration number: NMRR-20-177-53153(IIR)). Participants receiving CVD medicines or analgesics during dispensing process were recruited via convenience sampling technique between February and March 2020 at the Specialist Pharmacy Department of Jerantut Hospital, Malaysia. Refusal to medications and its reasons were asked based on the questionnaire developed by the researchers.Results: Overall, 175 patients participated in this survey and CVD drugs contributed toward 58.9% of the refused medicines. Those who refused CVD drugs and analgesics were significantly different in terms of gender, medications dosing frequency, refusal reasons namely side effects, medications use, intentionally skipping dose and skipping the dose when feeling well. No associations were found between forgetfulness and age with refusal to CVD drugs or painkillers. Those who refused CVD medicines had a significantly higher total daily medicines, total daily pill burden, and total number of medicines refused per prescription compared to those who refused analgesics. Cost of CVD medicines refused per prescription was significantly higher compared to analgesics, median Ringgit Malaysia (RM) 10.50 (IQR, RM 15.00) versus median RM 6.00 (IQR, 15.00), P=0.01.Conclusion: Refusal to CVD medicines and analgesics was associated with several medication’s and patient’s factors. However, higher cost-saving was observed in those refusing CVD medicines. Keywords: cardiovascular disease, analgesics, dispensing, wastage